Selective C5 nerve root block versus combined interscalene block for clavicle surgery - Çevikkalp, Eralp; Yapici, Furkan (The European Research Journal, 2022)
Objectives: The pain sensation of the clavicle is innervated by two separate plexuses. Regional anesthesia techniques for this area are challenging and complicated. Interscalene block, superficial cervical block, or a combination of these two is commonly used for regional anesthesia in clavicle surgery. The aim of this study was to investigate the efficacy of C5 nerve root block for clavicle surgery. Methods: Patients were divided into two groups: Group C5B (patients who received C5 nerve root block + superficial cervical plexus block) and Group ISB (patients who received interscalene block + superficial cervical plexus block). Motor block was assessed by the Medical Research Council Scale for Muscle Strength, while the sensory block of the areas corresponding to the nerve trace was assessed using the pinprick and cold testing. Furthermore, ultrasound was employed to evaluate phrenic nerve paralysis. Results: There was no difference between the groups in terms of mean age. The mean age of Group ISB was higher; however, the comparison of comorbidities revealed no significant difference between the groups. This statistically significant difference was clinically insignificant. Group C5B had lower 6-hour pain at rest, lower 0, 2, 4-hour pain on movement, and less postoperative analgesic consumption. Moreover, the time to first analgesic requirement was significantly longer in Group C5B. The motor examination of the peripheral nerves showed a significant difference in Group C5B. Conclusions: We are of the opinion that C5 nerve root block can be used instead of interscalene block since it does not produce a motor block in hand movements and preserves diaphragmatic functions. C5 nerve root block may therefore be considered an alternative to conventional interscalene block for clavicle surgery.